Digitalization Of The Aerodrome Control Tower Operation Logbook Based On The Website : Digitalisasi Logbook Pengoperasian Aerodrome Control Tower Berdasarkan Situs Web - Irfan; Irwan Jaya; Sadid Saneva; Muhrajan Piara (Jurnal Kolaboratif Sains, 2024)
This research focused on digitalizing a web-based Operational Logbook system for the Aerodrome Control Tower used by Air Traffic Controllers (ATC) at the Biak Sub-branch. The current manual Operational Logbook system, which relies on physical books and handwriting, is inefficient due to the need for substantial storage space and the susceptibility to damage. This research aimed to address these issues by providing a web-based application that facilitates easier, faster, and more efficient data entry and retrieval. This research method employed Rapid Application Development (RAD), effectively developing systems quickly and under urgent needs. The RAD process includes three stages: planning, system design, and implementation. The planning phase involved identifying user needs and application objectives. The system design phase encompasses the overall system architecture, while the implementation phase involves developing and testing the application. Results indicated that the web-based Operational Logbook application significantly simplifies the recording and reporting processes for ATC personnel, reduces errors in data entry, and enhances data accessibility. The digital logbook supports high mobility, eliminating the need for physical books and associated storage space, and provides a secure and easily accessible archive of records, minimizing the risk of data loss and misuse. In conclusion, the digitalization of the Aerodrome Control Tower Operational Logbook is crucial for ATC officers at the Biak sub-branch. This web-based application improves the efficiency and effectiveness of record-keeping and reporting processes, aligning with the demands of the digital era and reducing operational inefficiencies.